2011
DOI: 10.1016/j.sder.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Update on Photodermatoses

Abstract: Interactions with ultraviolet radiation (UVR) and chromophores in the skin happen on a daily basis. Photodermatoses, which are abnormal responses to UV exposure, can be classified into subgroups based on pathogenesis. This review will discuss the clinical features, pathogenesis, photobiologic evaluation, prognosis and therapies of the most common photodermatoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 39 publications
0
11
0
4
Order By: Relevance
“…It has been suggested that the formation of ROS in cells after treatment with aminoglycosides may play an important role in their toxicity . The overproduction of ROS may cause damage in DNA, proteins, and lipids, which may cause cell dysfunction or death . It has been stated that the presence of aminoglycosides in hair cells of the inner ear is correlated with increased oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the formation of ROS in cells after treatment with aminoglycosides may play an important role in their toxicity . The overproduction of ROS may cause damage in DNA, proteins, and lipids, which may cause cell dysfunction or death . It has been stated that the presence of aminoglycosides in hair cells of the inner ear is correlated with increased oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
“…When these excited state molecules return to their ground state, they transfer energy to surrounding oxygen, thereby inducing the generation of reactive oxygen species. The ROS cause cellular damage through the oxidation of lipids, nucleic acids and proteins [27,38]. ROS may react with both cellular and extracellular components, leading to induction of cytotoxicity, apoptosis, mutations and carcinogenesis [35].…”
Section: Discussionmentioning
confidence: 99%
“…166 CEP or Gunther disease is a rare autosomal recessive disorder, in which the defective enzyme is uroporphyrinogen III synthase, which leads to an accumulation uroporphyrinogen I and III in the bone marrow, blood, and other organs. 167 Patients have erythema, stinging, and photosensitivity, which lead to the formation of bullae within a day or 2 of exposure to the sun. Ulcerations and mutilating scarring of the ears, eyes, and nose can occur.…”
Section: Porphyriasmentioning
confidence: 99%